1997
DOI: 10.1074/jbc.272.24.15521
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Recognition of Specific DNA Targets by AlcR, a Zinc Binuclear Cluster Activator Different from the Other Proteins of This Class

Abstract: AlcR is the transactivator mediating transcriptional induction of the alc gene cluster in Aspergillus nidulans. The AlcR DNA-binding domain consists of a zinc binuclear cluster different from the other members of the Zn 2 Cys 6 family by several features. In particular, it is able to bind to symmetric and asymmetric sites with the same affinity, with both sites being functional in A. nidulans. Here, we show that unlike the other proteins of the Zn 2 Cys 6 binuclear cluster family, AlcR binds most probably as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 29 publications
(41 reference statements)
2
49
1
Order By: Relevance
“…This is in contrast to other Zn cluster proteins, which make strong contacts with two or more G residues in both strands of DNA (33). DMS footprinting (20) and nuclear magnetic resonance structural analysis of AlcR (6) revealed that the protein contacts two G residues (underlined) of the CGG triplet (5Ј-CGG-3Ј). Ppr1, a dimeric Zn cluster protein with almost the same sequence of the conserved recognition helix (5Ј-CRLKKIKC-3Ј) as Rgt1 (5Ј-CRKKKIKC-3Ј), directly interacts with the two G residues of the CGG triplet (22).…”
Section: Discussionmentioning
confidence: 97%
“…This is in contrast to other Zn cluster proteins, which make strong contacts with two or more G residues in both strands of DNA (33). DMS footprinting (20) and nuclear magnetic resonance structural analysis of AlcR (6) revealed that the protein contacts two G residues (underlined) of the CGG triplet (5Ј-CGG-3Ј). Ppr1, a dimeric Zn cluster protein with almost the same sequence of the conserved recognition helix (5Ј-CRLKKIKC-3Ј) as Rgt1 (5Ј-CRKKKIKC-3Ј), directly interacts with the two G residues of the CGG triplet (22).…”
Section: Discussionmentioning
confidence: 97%
“…Other work from this laboratory has already shown that the zinc binuclear cluster AlcR protein can bind as a monomer (8,22) and that the single sites play physiological roles in vivo (27). Residues of a monomer located in different places along the DNA binding domain could recognize the two half-sites of the NirA binding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…We have now carried out similar experiments with a NirA protein not carrying any GST sequences in order to eliminate any artifacts due to GST dimerization sequences, artifacts known to occur for the AlcR-DNA complex (22). We have extended the analysis to mutations in all nucleotides of the consensus sequence and have estimated quantitatively the effect of each mutation.…”
Section: Binding Of Nira Protein To Wild-type and Mutant Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Whereas many members of GAL4-type zinc cluster proteins known so far bind to a repeat, e.g., GAL4 (25), PPR1 (26), QA1F (4), the UaY repeat (42), HAP1 (53), and AlcR (19)(20)(21), the mode of binding of A. niger XlnR is still unclear, but in at least some promoters subject to XlnR control, the binding sites are present as repeats (e.g., spaced by 7 bp in the case of xlnD and 12 bp in the case of xlnA) (45). As mentioned before, we hypothesize that H. jecorina Ace1 occupies the right GGCTAA box under repressing conditions, while the left GGCTAA box is still contacted by Xyr1.…”
Section: Discussionmentioning
confidence: 99%